Minecraft : guide to animals - Gregory, Josh (Ann Arbor, Michigan : Cherry Lake Publishing, 2017)
Readers will learn everything they need to know about dealing with animals in the world of Minecraft, including how to tame them and harvest valuable resources from them.
Includes bibliographical references (page 31) and index.
5.6
5-8
740L
Keywords: Minecraft (Game) -- Juvenile literature; Video games -- Juvenile literature; Animals -- Juvenile literature; Minecraft (Game); Video games; Animals; Computer games